Therapeutic approaches to colorectal cancer via strategies based on modulation of gut microbiota - Chen, Maohua; Lin, Wei; Li, Nan; Wang, Qian; Zhu, Shaomi; Zeng, Anqi; Song, Linjiang (Frontiers in Microbiology, 2022)
The incidence of colorectal cancer (CRC) ranks third in the global malignant tumors and second in the death toll of malignant tumors. Gut microbiota is involved in the occurrence, formation, development, and response to different treatment measures of CRC. Under normal physiological conditions, intestinal microorganisms protect intestinal mucosa, resist pathogen invasion, and regulate the proliferation of intestinal mucosa cells through barrier effect and inhibition of DNA damage. The composition of gut microbiota and the influence of diet, drugs, and gender on the composition of flora are important information for early detection and prediction of CRC treatment results. Gut microbiota regulation is one of the most promising new strategies for CRC treatment in medicine, and it is very important to clarify the effect of gut microbiota on CRC and its possible mechanism for the prevention and treatment of CRC. Here, the review discusses the role of gut microbiota in the pathogenesis of CRC, the potential of the gut microbiota as a biomarker for CRC, and the therapeutic approach to regulating gut microbiota for CRC. It might provide new ideas for the use of gut microbiota in the prevention and treatment of CRC in the near future and reduce CRC incidence.